The Effect of Workload, Compensation and Employment Contract Agreement on Employee Turnover Intention at Pt Supra Ferbindo Farma - Hanafia, Fifi Hanafia; Supartono, Supartono; Wahyuningsih, Sri (Sean Institute, 2025)
This study examines the influence of Workload, Compensation, and Employment Contract Agreement on Turnover Intention among em-ployees at PT. Supra Ferbindo Farma. Using quantitative methods and questionnaires distributed to 82 respondents, the results show that Workload and Employment Contract Agreement have a positive and significant effect on Turnover Intention, while Compensation has no significant effect. Simultaneously, all three variables together influence employees’ intention to leave, with an R² value of 59.1%, indicating that 59.1% of turnover variation is explained by these variables, and 40.9% by other factors outside the study.